Phytochemical Evaluation of Extracts and GC-MS analysis of oil from Monodora myristica Seed - Obonga, Wilfred O; Omeje, Edwin O; Nnadi, Charles O; Ocheme, Wilson G (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Monodora myristica is one of the plants used extensively in folkloric medicine across West Africa. Despite the ethnopharmacological relevance of the plant, the phytochemical details, especially of the oil-rich seed, have not been completely elucidated. This study was designed to ascertain the phytochemical constituents of extracts of M. myristica seed oil and characterize the oil constituent using gas chromatography-mass spectrometry. The phytochemical screening was done using standard methods and the oil was characterized by GC-MS analysis. The result of the phytochemical screening showed the presence of terpenoids, sterols, saponins, tannins, flavonoids and cardiac glycoside in variable quantities. The GC-MS analysis revealed huge presence of fatty acids, terpenoids and other related compounds. The major compounds found in the oil of the seeds were o-cymene (2), γ-terpinene (3), nopinane (4), limonene (5), carvotanacetone (6), β-pinene (7), aromadendrene (9), germacrene (11), α-amorphene (13) and copaene (14). The rich phytoconstituents present in the seed oil could be the basis of its acclaimed ethnomedicinal uses across West Africa and beyond. Dhaka Univ. J. Pharm. Sci. 18(1): 69-73, 2019 (June)